FORMATION OF THE EFFECTIVENESS OF PUBLIC AND PERSONAL SECTOR COMPANIES OF THE MARITIME INDUSTRY SUPPORTED AN INTEGRATED ANALYSIS OF ECONOMIC RESULTS - IAYA ANDREN, DR. KRIDS SÁNCHEZ (International Journal of Multidisciplinary Research and Studies, 2020)
The maritime industry in Lithuania is predicated on the general public, state, and personal sectors, and on the interests, activities and partnership of business companies operating within the aforementioned sectors. Despite the management of the general public sector in Lithuania being criticized for showing performance shortcomings, the state of Klaipeda’s seaport management and performance results refutes this criticism. The general results of partnerships and co-operation is obtained – it reflects the port’s competitiveness level within the region. Consistent with a report conducted by the International fund, the potential output growth in 2014–2015 has declined since the world financial crisis. Policy actions are required to spice up the productivity levels, and to foster capital growth. so as to attain these objectives, it’s essential to grasp the company’s financial situation better, because the higher the financial state of the corporate, the more new port service users, cargo owners, shipping lines, and investors it attracts. The quality analysis of economic indicators is insufficient. Hence the strategy of integrated analysis is applied. The results of it’d be considered as guidelines for both the state seaport authorities so as to boost the port’s competitive position within the region, and for the private companies for his or her business development.